2020
DOI: 10.1038/s41598-020-77438-8
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of qSOFA calculated at triage and during emergency department treatment to rapidly identify sepsis patients

Abstract: The quick sequential organ failure assessment (qSOFA) score has been proposed as a means to rapidly identify adult patients with suspected infection, in pre-hospital, Emergency Department (ED), or general hospital ward locations, who are in a high-risk category with increased likelihood of “poor outcomes:” a greater than 10% chance of dying or an increased likelihood of spending 3 or more days in the ICU. This score is intended to replace the use of systemic inflammatory response syndrome (SIRS) criteria as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Our result is consistent with recent studies that emphasized the poor performance of qSOFA in the prediction of sepsis mortality. [16,17] A retrospective study by Moskowitz et al [18] found that the qSOFA had a sensitivity and specificity of 39% and 87%, respectively, when used in predicting in-hospital mortality at the time of ED presentation among 24,164 patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is consistent with recent studies that emphasized the poor performance of qSOFA in the prediction of sepsis mortality. [16,17] A retrospective study by Moskowitz et al [18] found that the qSOFA had a sensitivity and specificity of 39% and 87%, respectively, when used in predicting in-hospital mortality at the time of ED presentation among 24,164 patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Existing scores and rapid troponin pathways do not provide information regarding the risk of a non-coronary diagnosis being present, which partially limits their utility in facilitating early discharge. Several pre-hospital scores (such as NEWS, MEWS, PMEWS) are aimed at determining critically unwell patients for transport to hospital, but the focus of these has been to identify patients at risk of imminent deterioration rather than patients that need further investigation or are safe for early discharge [20] , [21] , [22] , [23] . To our knowledge, the ECAMM risk score model is the first clinical risk score addressing this need, and discriminatory performance for the composite outcome, and its individual components, was substantially higher in comparison to the HEAR and EDACS scores.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the specificity and PPV of the HOPE Sepsis Score to predict the risk of sepsis were lower in patients with intermediate than those with high-risk for sepsis, respectively (specificity: 80.3 vs. 99.2% and PPV: 32.4 vs. 66.1%). However, the sensitivity and specificity of qSOFA ≥ 2 to predict in-hospital mortality were 69 and 55.5%, respectively (21). In 2,112 patients suffering from infections, the calculation of systemic inflammatory response syndrome (SIRS) and qSOFA showed a sensitivity of 52.8 and 19.5% and a specificity of 52.5 and 92.6% for 28-day mortality (22).…”
Section: Hope Sepsis Scorementioning
confidence: 99%